A 'demand-supply-regulation-institution' stakeholder partnership model of delivering zero carbon buildings. (November 2020) - Pan, Wei; Pan, Mi
Highlights: Zero carbon building (ZCB) delivery should be addressed as a socio-technical system. A systems framework of ZCB delivery is established with four system components. Stakeholders of ZCB delivery are in demand, supply, regulation, institution groups. Eight major stakeholder partnerships of promoting ZCB are reviewed. A stakeholder partnership model is developed based on two theoretical frameworks. Abstract: In addressing anthropogenic climate change, many countries have tightened up their building energy regulations and even formulated zero carbon building (ZCB) policies. However, there still lacks real-world uptake of the ZCB approach. The importance of stakeholder engagement and partnership to effectively promote and deliver ZCBs has been emphasized but insufficiently understood. This paper aims to develop a stakeholder partnership model of delivering ZCBs in a systematic manner. Theoretically, the model is based on a socio-technical systems framework that covers four socio-technical system components of delivering ZCBs and a stakeholder framework that categorizes the many stakeholders of buildings and the process of building. Empirically, the model draws on the review and examination of seven major stakeholder partnerships worldwide for promoting ZCB. Integrating all findings, a demand-supply-regulation-institution (DSRI) stakeholder partnership model is developed for successfully achieving the zero carbon target for future buildings. This developed model links different stakeholder groups to address the socio-technical systems of delivering ZCBs in the geographical, socio-economic, and political and regulatory contexts. The model was contextualized and validated using an in-depth case study with the Hong Kong Zero Carbon Partnership. Fourteen strategies were yielded for supporting the application of the model and informing future ZCB practices.